Molecular mechanisms governing circulating immune cell heterogeneity across different species revealed by single‐cell sequencing - Li, Zhibin; Sun, Chengcheng; Wang, Fei; Wang, Xiran; Zhu, Jiacheng; Luo, Lihua; Ding, Xiangning; Zhang, Yanan; Ding, Peiwen; Wang, Haoyu; Pu, Mingyi; Li, Yuejiao; et al. (Clinical and translational medicine, 2022)
Background Immune cells play important roles in mediating immune response and host defense against invading pathogens. However, insights into the molecular mechanisms governing circulating immune cell diversity among multiple species are limited. Methods In this study, we compared the single‐cell transcriptomes of immune cells from 12 species. Distinct molecular profiles were characterized for different immune cell types, including T cells, B cells, natural killer cells, monocytes, and dendritic cells. Results Our data revealed the heterogeneity and compositions of circulating immune cells among 12 different species. Additionally, we explored the conserved and divergent cellular crosstalks and genetic regulatory networks among vertebrate immune cells. Notably, the ligand and receptor pair VIM‐CD44 was highly conserved among the immune cells. Conclusions This study is the first to provide a comprehensive analysis of the cross‐species single‐cell transcriptome atlas for peripheral blood mononuclear cells (PBMCs). This research should advance our understanding of the cellular taxonomy and fundamental functions of PBMCs, with important implications in evolutionary biology, developmental biology, and immune system disorders. Our study compared the single‐cell transcriptomes of immune cells from 12 species. The results revealed the heterogeneity and compositions of circulating immune cells. We explored the conserved and divergent cellular crosstalks and genetic regulatory networks among vertebrate immune cells.